Where Old Meets New: New Life for Old Ruins - Erşan, Şevkat; Özkan, Hilal (ICONARCH International Congress of Architecture and Planning, 2017)
Ruins: buried cities brought to light by archaeologists in every part of the world; sacred temples dedicated to divinities that we have ceased to worship; towers, forts, strongholds, military defences made useless by the unremitting development of new weapons; industrial plants and factories no longer compatible with modern techniques of production and abandoned like the carcasses of huge old-fashioned cars; buildings that have been gnawed, mutilated and reduced to a state that bears no relation to their original purpose; buildings that have sometimes deteriorated to a point where their original form can hardly be recognised; buildings that only survive in the form of isolated fragments. Ruins form a considerable part of our architectural heritage and, actually, even of the World Heritage List: they are preserved as ruins, maintained as ruins and visited by a growing number of people who, in ruins, see values, significance and meaning – in spite of their condition. When dealing with such ruined structures, several different problems and issues are faced and different philosophical approaches and strategies are involved depending on the hierarchy of values for the different categories of buildings. Monuments with high historic and age values are often preserved in their existing form as ruins, avoiding any interventions that endanger these values. On the other hand, in less important buildings with regard to their historic and age values, and mainly when the largest part of their structure is maintained in a good condition, special consideration is given for their reuse and social revival. In this paper, several case studies are presented regarding the conservation of historic ruins in around the world but mostly in United Kingdom, showing the positive and negative consequences of different philosophies and approaches followed in each case. Through these examples, the different concepts of conserving historic complexes – such as ‘museum’ conservation, final form of ruins, matters of authenticity, dynamic maintenance, compatibility of materials, structural reinforcement – are discussed.